Synthesis and Characterization of Keratin-Based Scaffold for Potential Tissue Engineering Applications - Murugiah Krishani; Jia Ning Chong; Wan Rong Lim; Norwahyu Jusoh; Nonni Soraya Sambudi; Hazwani Suhaimi (Fibers)
Keratin, a fibrous structural protein, has been employed as a biomaterial for hemostasis and tissue repair due to its structural stability, mechanical strength, biocompatibility, and biodegradability. While extensive research has focused on developing scaffolds using keratin extracted from various sources, no studies to date have explored the use of keratin derived from human nail clippings. In this study, keratin was extracted from human nail clippings using the Shindai method and used to fabricate and compare two types of scaffolds for bone tissue engineering via the freeze-drying method. The first scaffold consisted of keratin combined with gelatin (KG), while the second combined keratin, gelatin, and hydroxyapatite (HAp) (KGH), the latter synthesized from blood cockle clam shells using the wet precipitation method. Physicochemical characterization and surface morphology analysis of keratin and both scaffolds showed promising results. Tensile strength testing revealed a significant difference in Young’s modulus. The KG scaffold exhibited higher porosity, water uptake, and water retention capacity compared to the KGH scaffold. In vitro biocompatibility studies revealed that the KGH scaffold supported higher cell proliferation compared to the KG scaffold. This study demonstrates the potential of using human nail-derived keratin in composite scaffold fabrication and serves as a foundation for future research on this novel biomaterial source.